Pengaruh Pembuatan Tutorial Terhadap Peningkatan Pemahaman Petugas Rekam Medis di Fasilitas Pelayanan Kesehatan tentang Pengisian Data pada Aplikasi SIDeKa-Pro - Hikmawan Suryanto; Madihah Madihah (Poltekkes Kemenkes Semarang, 2022)
Medical record officers who are late in filling out data on SIDeKa-Pro application in 2020 are 53% and for January-March 2021 period are 31%. They were late in filling because there was no procedure and did not understand how to fill in the data. The purpose of this study was to determine the effect of making tutorials in the form of manuals and video tutorials on the level of understanding of medical record officers in health care facilities about data entry in the SIDeKa-Pro application. The research design used pure experimental, namely one group pretest and posttest experimental research. The population and sample are medical record officers who are in charge of data entry in SiDeKa-Pro application, as many as 24 people. The sampling technique used was purposive sampling. The results of the Wilcoxon test, the p-value is 0.000 (p-value 0.05). It can be concluded that there is an influence between the provision of tutorials in the form of manuals and videos on the level of understanding of health care facility managers about data entry in the SIDeKa-Pro application. The conclusion is that making tutorials has an effect on increasing the understanding of medical record officers in health care facilities.